PENGARUH IMPLEMENTASI EXPERIENTAL MARKETING TERHADAP LOYALITAS MEMBER TOKO ALFA BUSANA DI SUKOWONO - Khoiruzzaki, Kiky; Hafidzi, Achmad Hasan; Reskiputri, Tatit Diansari (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Experiential marketing is a method of providing information about a product or service. Experiential marketing will allow customers to differentiate products and services from one another because they can directly feel and experience the experience through five channels (sense, feel, think, act, related), both before and during the consumption of the product or service. The purpose of this study is to prove the magnitude of the influence of experiential marketing on the loyalty of Alfa fashion store members in Sukowono. This study uses quantitative methods. And the sampling technique used in this study is to use non-probability sampling, which is the technique used in sampling that uses predetermined criteria. While the objects of this research are Alfa fashion member card holders and customers aged 15-70 years, where at that age is a productive age which has met the criteria for member loyalty. The results of this study prove that sense, feel, think, and relate have a significant effect on the loyalty of members of alpha clothing, while act has no significant effect on loyalty of members of alpha clothing.